2018
DOI: 10.4236/cc.2018.62002
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigations on the π-π Stacking Interactions in Phenol-Water Complexes

Abstract: Non covalent interactions are quite common in all kinds of π-systems, such as π-π interactions, long range/short range van der waal force of interactions, ion-π interactions etc. Ab initio calculations are well established and account well for the experimental long range interaction energies for small clusters of aromatic molecules and most of the calculations were carried out using the MPn methods. If a reasonably large basis set is used to calculate the stacking interaction energies for a cluster (dimer, tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In terms of toxicity, trivalent arsenicals are more toxic and mobile than pentavalent ones, which is related to the speciation and its affinity with the -SH groups in biomolecules such as glutathione and cysteinyl residues in enzymes [55][56][57]. In the first place, trivalent arsenicals are deprotonated above pH=9.2; then, trivalent arsenicals are neutrally charged at neutral and physiological pH [55,58].…”
Section: Resultsmentioning
confidence: 99%
“…In terms of toxicity, trivalent arsenicals are more toxic and mobile than pentavalent ones, which is related to the speciation and its affinity with the -SH groups in biomolecules such as glutathione and cysteinyl residues in enzymes [55][56][57]. In the first place, trivalent arsenicals are deprotonated above pH=9.2; then, trivalent arsenicals are neutrally charged at neutral and physiological pH [55,58].…”
Section: Resultsmentioning
confidence: 99%
“…Conformational diversity in the gas phase may in some cases be much more pronounced than in solution or crystal. [4][5][6][7] Recently, we have shown that the iodotriflamidation at the two C=C bonds in 1,1,3,3-tetramethyl-1,3-divinyldisiloxane affords two new heterocycles, 6-iodo-3-(triflamidomethyl)-4-triflyl-1,-4,2,7-oxazadisilepane 1 and 2,2,4,4-tetramethyl-6,8-bis (triflyl)-3-oxa-6,8-diaza-2,4-disilabicyclo[3.2.2]nonane 2 via the intermediate N,N'-(1,1,3,3-tetramethyldisiloxane-1,3-diyl)bis(2-iodoethane-2,1-diyl)bistriflamide undergoing two successive dehydroiodination reactions to give compounds 1 and 2, respectively. 8 The structure of both compounds was proved by single crystal X-ray diffraction.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, due to a very short time of interaction of the diffracting electron with a single molecule, ~10 −18 s, the GED method is able to provide information on rather fast conformational transitions, as compared with the NMR method. Conformational diversity in the gas phase may in some cases be much more pronounced than in solution or crystal 4–7 …”
Section: Introductionmentioning
confidence: 99%
“…Arsenicals are highly toxic compounds whose chronic exposure has been associated with carcinogenic, endocrine, cardiovascular diseases, skin and lung damage, diabetes, and metabolic syndrome [1][2][3][4]. The arsenic toxicity is related to its ability to replace phosphate groups in biomolecules, showing a strong affinity with −SH groups of cysteinyl residues [5,6].…”
Section: Introductionmentioning
confidence: 99%